Analisis Hubungan Komunikasi, Kepemimpinan dan Disiplin Kerja Terhadap Kepuasan Kerja Karyawan - Muhammad Alfaridzi Batu Bara; Mas Intan Purba; Fitriyani Pasarib; Ryan Mauliza T; Nurul Wardani Lubis (Journal of Management and Bussines (JOMB), 2023)
This study aims to examine and analyze the effect of Promotion, Service Quality and Consumer Satisfaction on Gojek Consumer Loyalty (Case Study on Law Faculty Students at Prima University of Indonesia). The research method used is quantitative. Total population of 208 students and 68 employees as research samples. The sampling technique used is random sampling. The results showed that promotion partially had a positive and significant effect on Gojek Consumer Loyalty. Service Quality has a positive and significant effect on Gojek Consumer Loyalty. Consumer Satisfaction has a positive and significant effect on Gojek Consumer Loyalty. Promotion, Service Quality and Consumer Satisfaction have a positive and significant effect on Gojek Consumer Loyalty. In conclusion, promotion level, service quality and customer satisfaction have a role in customer loyalty. Keywords: Customer Satisfaction Service Quality, Consumer Loyalty, Promotion